2002
DOI: 10.1002/polb.10377
|View full text |Cite
|
Sign up to set email alerts
|

Biospinning: Change of water contents in drawn silk

Abstract: Changes of the water content in drawn silk during drying were investigated by thermal analysis and 1H pulse NMR. Water in liquid silk by drawing extruded from the inside of the silk filament into ambient air. The water contents in the drawn silk decreased with drying time. Assuming the nonfreezing water has a concentration of 10 wt % in the liquid silk, the percentage distribution of water in liquid silk is composed of 10 wt % nonfreezing water, 40 wt % freezing water, and 30 wt % free water. This 40 wt % free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Many analytical methods including Raman, near infrared (IR), , IR, , dynamic scanning calorimetry (DSC), thermogravimetric analysis (TGA), , X-ray diffraction (XRD), dynamic mechanical thermal analysis (DMTA), electron spin resonance (ESR), nuclear magentic resonance (NMR) and so on have been used for this purpose. They have provided many insights into the molecular structure and dynamics of SF in the hydrated state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many analytical methods including Raman, near infrared (IR), , IR, , dynamic scanning calorimetry (DSC), thermogravimetric analysis (TGA), , X-ray diffraction (XRD), dynamic mechanical thermal analysis (DMTA), electron spin resonance (ESR), nuclear magentic resonance (NMR) and so on have been used for this purpose. They have provided many insights into the molecular structure and dynamics of SF in the hydrated state.…”
Section: Introductionmentioning
confidence: 99%
“…They have provided many insights into the molecular structure and dynamics of SF in the hydrated state. In general, water in the silk–water system can be divided into three categories: free water, freezing bound water, and nonfreezing bound water. , Recently, we could identify further distinct components of the freezing bound water in the 2 H solution NMR relaxation measurements for water in SF fibers. , However, a complete picture of the structure and dynamics of SF is still not well understood at the molecular level. Because of the heterogeneous dynamic character (distribution from mobile to immobile domains) of SF in the hydrated state, the 13 C solid-state NMR observations, which emphasized the mobile and immobile components in SF, are very effective for the characterization of the hydrated SF.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular grafts are generally used in a hydrated state, and the mechanical properties of SF molecules change remarkably because of the effect of water. , Therefore, it is critical to understand the structure and dynamics of SF grafts and the SF sponge coatings in the hydrated state during the development of SF vascular grafts. Numerous analytical methods including Raman, IR, dynamic scanning calorimetry, thermogravimetric analysis, , X-ray diffraction, dynamic mechanical thermal analysis, and NMR among others have been used for the purpose. They have provided numerous insights into the structure and dynamics of SF molecules in the hydrated state.…”
Section: Characterization Of Sf Grafts In the Hydrated Statementioning
confidence: 99%
“…In general, water in the silk–water system can be divided into three categories: free water, freezing bound water, and nonfreezing bound water. , , Recently, more distinct components of the freezing bound water were identified from 2 H solution NMR relaxation property measurements for water in SF fibers. , Figure shows two-dimensional 2 H T 1 – T 2 correlation map of 2 H 2 O in a 2 H 2 O–SF fiber system at 25 °C. T 1 denotes spin–lattice relaxation time, and T 2 represents spin–spin relaxation time.…”
Section: Characterization Of Sf Grafts In the Hydrated Statementioning
confidence: 99%
“…Especially, the study of carbonization behavior is much minor. Some articles treat the thermal decomposition of tussah SF below 300°C,19–26 but we only know one article concerning carbonization behavior; that is, Nishikawa et al reported the carbonization behavior and some characters for mulberry silk and tussah silk 27…”
Section: Introductionmentioning
confidence: 99%